Procalcitonin-Guided Antibiotics after Surgery for Peritonitis: A Randomized Controlled Study - Juliette C. Slieker; Steve Aellen; Philippe Eggimann; Valentine Guarnero; Markus Schäfer; Nicolas Demartines (Gastroenterology Research and Practice)
Background. Serum procalcitonin (PCT) is a useful biomarker to tailor the duration of antibiotics in respiratory infections. The objective of this study was to determine whether PCT levels could tailor postoperative antibiotic therapy in patients operated for peritonitis. Method. Patients with peritonitis were randomized postoperatively. The control group received antibiotics for a defined duration according to institutional guidelines. In the study group, antibiotics were stopped based on serum PCT levels. Patients were stratified into three categories: (1) gastrointestinal perforation, (2) perforated appendicitis, and (3) postoperative complication. Primary outcome was duration of antibiotics. Results. We included 162 patients: 83 and 79 patients in the control group and study group, respectively. In the subgroup of patients with peritonitis due to gastrointestinal perforation, we found 7 days of antibiotics in the PCT group versus 10 days in the control group (p value 0.065). There was no difference in infectious complications, mortality, median length of hospital stay, and necessity to restart antibiotics. Conclusion. No significant differences were found in duration of antibiotics when applying PCT guidance. However, in the subgroup of primary perforation of the gastrointestinal tract, there was a difference in duration of antibiotics in favor of the PCT group without obtaining significance, as the study was not powered for subgroup analysis. Further studies including only this subgroup should be performed.